Analisis Wisata Dusun Bambu Terhadap Perubahan Sosial Ekonomi Masyarakat Kampung Cijanggel, Kabupaten Bandung Barat - Mutiara Mutiara; Nur Aini Hunafa (Lembaga Pengembangan Kinerja Dosen, 2024)
The state of the community surrounding Dusun Bambu following the emergence of Dusun Bambu tourism in the Cijanggel Village region served as the driving force behind this study. These results have established Dusun Bambu's role and influence over the residents of Cijanggel Village. The arrival of Dusun Bambu tourism resulted in a shift in the living standards of the residents of Cijanggel Village.Among other things, the study's goals are to: 1) determine how much Dusun Bambu tourism has benefited the locals of Cijanggel Village; 2) determine the locals' standard of living following the establishment of Dusun Bambu tourism; and 3) determine the impact of Dusun Bambu tourists on the locals' social lives